2012
DOI: 10.1097/iae.0b013e3182173753
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Chamber Aqueous Flare Is a Strong Predictor for Proliferative Vitreoretinopathy in Patients With Rhegmatogenous Retinal Detachment

Abstract: Our study shows that the breakdown of the blood-ocular barrier as determined by aqueous flare is a major risk factor for PVR redetachment. The laser flare-cell meter is a fast, noninvasive, and safe tool that allows predicting the PVR redetachment risk preoperatively. It provides the surgeon with an estimate to choose those patients who could benefit from intravitreal drugs to prevent PVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 9 publications
7
46
2
3
Order By: Relevance
“…Laser flare photometry is a potent tool to estimate preoperatively the individual risk of patients with RD to develop PVR in the later course after initially successful re-attachment surgery 3. In the present study we confirmed these previous results in an independent cohort.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Laser flare photometry is a potent tool to estimate preoperatively the individual risk of patients with RD to develop PVR in the later course after initially successful re-attachment surgery 3. In the present study we confirmed these previous results in an independent cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Exclusion criteria included active vasculitis, active uveitis, proliferative diabetic retinopathy, diabetic macular oedema, neovascular age-related macular degeneration, retinal vein occlusion and preoperative PVR grade C. All patients were enrolled for the study. There was no overlap with the previously reported cohort 3. All surgery was performed by one of four experienced vitreoretinal surgeons, who were aware of flare values preoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the sensitivity and specificity of preoperative flare at different cut-off values were too low to adequately filter out the high-risk patients. As a consequence, we were unable to validate the findings of Schroder et al ,13 although they used the same flare metre type and calibration protocol.…”
Section: Discussionmentioning
confidence: 75%
“…A different potential predictor for PVR development was found by Schroder et al 13. They found preoperative anterior chamber flare—caused by reflection of laser light by proteins in aqueous humour—to be a strong predictor for PVR development.…”
Section: Introductionmentioning
confidence: 86%
“…Instead of conventional slit-lamp microscopy, the LFCM provides an accurate and reproducible method for evaluating BAB dysfunction [5]. Numerous studies have quantified BAB breakdown in patients with uveitis and acute angle-closure glaucoma and in patients after cataract surgery, penetrating keratoplasty, and panretinal photocoagulation [6,7,8,9,10,11,12,13,14]. However, to the best of our knowledge, few studies so far have reported breakdown of the BAB after ocular trauma.…”
Section: Discussionmentioning
confidence: 99%